Two Varieties Test Of Cauliflower (Brassica oleracea L.) Growth and Production After Application Of Phytomic Microfertilizers On Lowland Lands - Akhmad Sopian; Cris Yan Tomy; Hamidah Hamidah; Oktavianus Oktavianus (University of Prof. Dr. Hazairin, SH, 2022)
The prospect of cauliflower or in its foreign language cauliflower in east Kalimantan is very promising. The supply of cauliflower at this time is very dependent on outside the East Kalimantan region, namely Java and Sulawesi. The efforts made to meet the needs are to increase production by improving intensive cultivation techniques. The productivity of cauliflower plants can be increased by providing micronutrients and using suitable varieties. The study aims to determine the effect of mikro fitomic and variety nutrients on the growth and production of cauliflower plants. This study was compiled in a Randomized Group Design (RAK) with a 4 x 2 factorial trial with 4 repeats. The first factor is the concentration of mikro fitomic fertilizer (F), which consists of 4 levels: F0: control, F1: 1.5 ml/litre of water, F2: 2.5 ml/litre, F3: 3.5 ml/litre water. The second factor is the variety, which consists of 4 levels V2: PM 126 variety. Fitomic micro fertilizer has significantly affected the growth and production of Brassica oleracea. The crop/plant weight of 884.38 grams was achieved at the optimal concentration of micro-fitomik fertilizer 3.5 ml/litre of water. The Brassica oleracea variety had a significantly affected diameter, plant/plant weight, and plant/plot weight. Plant production/hectare of the PM 126 variety was higher than the production of the Orient variety. The interaction between the concentrations of micro-fitomic fertilizers and the two types of varieties was not significantly different in growth and production. Recommendations for the application of micro-fitomic to B.oleracea plants are applied at a concentration of 3.5 ml/litre of water. PM126 and Orient varieties are suitable for cultivation in the lowlands of East Kalimantan.